Динамічні процеси в тонкому циліндрі при тепловому опроміненні торця - Бойчук, О.В.; Сенченков, І.К.; Жук, Я.О. ("Доповіді НАН України", 2007)
The processes of generation and propagation of a stress pulse and temperature variations caused by a thermal impact at the face of a long thin steel cylinder are investigated. The statement of the dynamic coupled problem of thermomechanics is used along with the thermodynamically consistent theory of the inelastic behavior of a material. It is solved numerically by the finite element method. Main properties of a thermomechanical state in the vicinity of the irradiated end and the stress pulse propagation accompanied with the temperature variation are studied. Relations between the parameters of a thermal pulse and a stress wave are established.